Cleaning Sea Water from Petroleum Products by Using Rubber Powder - Marsoglu, Muzeyyen; Topuz, Ahmet; Erdogmus, Ali; Yurdalan, Oguzhan; Bilgin, Sertac; Feyzioglu, Ahmet; Topuz, Polat; Karahan, Tuba (CARL HANSER VERLAG, 2011)
For the study behind this report, Shell Donax TC 30 oil is added by percentages of 1 and 2 vol.-% to sea water samples which are taken from the beach of Florya near Istanbul in Turkey. Additionally, active and inactive rubber powder has been added by various percentages of 1, 2, and 5 vol.-% to such mixtures. After this, the result of cleaning process efficiency has been investigated after 1, 3, and 5 minutes. For comparison, carbon black has been used in another series of experiments. At the end of the different time periods, the process of cleaning by using rubber powders shows that a cleaning of over 98 % is achieved. During the cleaning process it is observed that oil is absorbed by the rubber powder and that its size becomes larger. The results make evident that rubber powders can be easily used in such new cleaning processes (at least 4 times) after the respective drying.
Keywords: Materials Science